An integrated inventory models under cooperative and non-cooperative seller-buyer and vendor supply chain - Shahrjerdi, Reza; Mohd Ariffin, Mohd Khairol Anuar; Mustapha, Faizal; Ismail, Napsiah; Esmaeili, Maryam (Academic Journals, 2011)
The first level of the supply chain basically contains three distinguished levels; these are single buyer (that is retailer), the second level vendor (that is warehouse) and single seller in the third level. The aim of this study was to investigate the cooperative of inventory models among the players in a three-level supply chain. In addition, the challenges involved in determining the optimal value of time interval between consecutive setups and orders in a coordinated inventory model were also taken into consideration. For this purpose, the researchers selected three types of non-cooperative models; nonetheless, the primary focus of this model is to reduce the coordinated total relevant cost to the minimum. This was followed by the implementation of recompense policy for the losses and profits of the coordinated inventory model proposed in the present study. The method which offers an optimal solution for the model developed in this study was obtained, whereas a numerical example was also given and demonstrated.